The Effect of Technology Utilization and Modernization of The Tax Administration System on The Compliance of Individual MSME Taxpayers in The City of Samarinda - Moa Bora, Ferdinandus; Asmapane, Set (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study aims to determine the effect of technology utilization and modernization of the tax administration system on the compliance of MSME taxpayers in Samarinda City. This type of research is quantitative research using primary data and measured using the Likert scale. The number of samples used in this study was 100 respondents of individual MSME taxpayers in Samarinda City which was determined using purposive sampling. This study used multiple linear regression analysis method processed through SPSS (Statistical Product and Service Solutions) version 26 program. The results of this study show that simultaneously the variables of technology utilization and modernization of the tax administration system have a positive and significant effect on the compliance of individual MSME taxpayers. Meanwhile, partially the variable of technology utilization has a positive and significant effect on the compliance of individual MSME taxpayers and the modernization of the tax administration system has a positive and significant effect on the compliance of individual MSME taxpayers.